The history of science and medicine in the context of COVID‐19. (27th July 2020) - Charters, Erica; McKay, Richard A.
Abstract: This spotlight issue encourages reflection on the current COVID‐19 pandemic, not simply through comparisons with previous epidemics, but also by illustrating that epidemics deserve study within their broader cultural, political, scientific, and geographic contexts. Epidemics are not solely a function of pathogens; they are also a function of how society is structured, how political power is wielded in the name of public health, how quantitative data is collected, how diseases are categorised and modelled, and how histories of disease are narrated. Each of these activities has its own history. As historians of science and medicine have long pointed out, even the most basic methodologies that underpin scientific research—observation, trust in numbers, the use of models, even the experimental method itself—have a history. They should not be taken as a given, but understood as processes, or even strategies, that were negotiated, argued for and against, and developed within particular historical contexts and explanatory schemes. Knowing the history of something—whether of numbers, narratives, or disease—enables us to see a broader range of trajectories available to us. These varied histories also remind us that we are currently in the midst of a chaotic drama of uncertainty, within our own unstable and unfolding narrative.